Analysis of electric field influence on buildings under high‐voltage transmission lines. Issue 4 (1st July 2016) - Tong, Ziyuan; Dong, Zhaoyang; Ashton, Trevor
Abstract : High‐voltage cables especially bare cables generate intense electric fields. Within certain distances, the fields could have strong effects on human health. Since of housing planning factors, it is inevitable that there will be buildings located under bare cables. Whether the intensity of electric field exceeds safety level (5 kV/m at 50 Hz) has been a concern for both land agents and residents. To address the concerns, this study studies the electric field of 500 kV overhead transmission line exerted on building and proposes the scheme for field intensity reduction. The authors study shows that when overhead cable and building are in different relative locations, the maximum intensity and influence range in the window regions can be highly variable, which suggests an optimal building orientation to minimise the electric field generated by overhead transmission lines. They also studied the field distribution in window regions on each floor in two models. The results provide design basis for safe distance between buildings and transmission lines. A shielding scheme for building construction is proposed to reduce the field intensity. Experiment result shows that with shielding on the building roof at a certain angle, the influence of electric field can be effectively reduced.